Digital education to counter the dominance of the culture of insignificance in the networked society: A critical descriptive study - عبد الكريم بوعبيبسة; فضيلة تومي (International Journal of Social Communication, 2022)
This scientific paper will address the problem of the peripheral relationship that exists between digital education and the culture ofinisignificance or the culture of nonsense, as it is now called Alain Denault, against the background of the variables generated by the output of the network community in accordance with the perspective put forward by Manuel Castells, especially after the widespread spread of digital platforms and their effects and effects on negative sales and the fallout of thought and meaning, as a result of the intensive use of these cultural products. And that's why we're going to try to decipher this composite equation, show what digital education can do in the throwaway of interactions in the digital environment, where the role of the gatekeeper is decreasing, and give way to the Machiavellian principle of profit and capital growth according to a purely pragmatic view of wealth growth, even at the expense of the human and social values of the individual and society.